Paternity Coaching During the Transition to Fatherhood - Kate Smith (International Journal of Evidence Based Coaching and Mentoring, 2020)
The transition to parenthood is one of the most joyful, yet stressful life events, however, there is little evidence to support paternity coaching as an intervention. This action research study draws on gender studies and maternity and transition coaching literature to inform the research. A cohort of four fathers participated in the research, each receiving three coaching sessions, followed by an interview. Themes emerging were responsibility, self-care and adapting to the new role. Practitioners and academics will find the research helps in understanding the themes supporting transition coaching for fathers, and in identifying further gaps for future research.